2016
DOI: 10.1016/j.fertnstert.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral, cognitive, and motor performance and physical development of five-year-old children who were born after intracytoplasmic sperm injection with the use of testicular sperm

Abstract: The long-term effects on development and health in children born after TESE-ICSI procedures seem to be reassuring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…This finding was replicated and extended to the age of 9 years in the current study. Yet, Meijerink et al [16] reported that 5year-old children born after IVF with ICSI scored significantly below the norms of the general population on a standardized motor test. This difference may, however, be attributed firstly to the large proportion of twins studied (about one third of the study group), and secondly to the use of a specific form of ICSI, i.e., testicular sperm extraction ICSI.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was replicated and extended to the age of 9 years in the current study. Yet, Meijerink et al [16] reported that 5year-old children born after IVF with ICSI scored significantly below the norms of the general population on a standardized motor test. This difference may, however, be attributed firstly to the large proportion of twins studied (about one third of the study group), and secondly to the use of a specific form of ICSI, i.e., testicular sperm extraction ICSI.…”
Section: Discussionmentioning
confidence: 99%
“…SRR varies according to the histopathological diagnosis as well as the cause of NOA. Very reassuring reports of the health of the children born after TESE‐ICSI have been published . Some data are available on cumulative live birth rates after the diagnosis of NOA.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is encouraging to note that even the most recent studies have confirmed that ICSI and IVF children have similar cognitive, motor and language development as their naturally conceived counterparts (Balayla et al 2017). These results are not only true for ejaculated specimens but also for ICSI performed with testicular sperm (Meijerink et al 2016).…”
Section: Developmental Outcomesmentioning
confidence: 83%